Functional expression of oxidative phosphorylation proteins in the rod outer segment disc. (16th January 2013) - Panfoli, Isabella; Calzia, Daniela; Bruschi, Maurizio; Oneto, Michele; Bianchini, Paolo; Ravera, Silvia; Petretto, Andrea; Diaspro, Alberto; Candiano, Giovanni
Abstract : The rod Outer Segment (OS) disc, an organelle devoid of mitochondria, is specialized in phototransduction, a process requiring a continual chemical energy supply. We have shown that OS discs express functional mitochondrial electron transport chains, Fo F1 ‐ATP synthase and the tricarboxylic acid cycle enzymes, all mitochondrial features. Here, we focus on oxygen consumption and adenosine triphosphate (ATP) synthesis by OS discs analysing electron transport chain I‐III‐IV and II‐II‐IV pathways, supported by reduced nicotinamide adenine dinucleotide and succinate, respectively. Interestingly, respiratory capacity of discs was measurable also in the presence of 3‐hydroxy‐butyrrate, a typical metabolic substrate for the brain. Data were supported by a two‐dimensional electrophoresis analyses conducted as our previous one, but focused to those mitochondrial proteins that are involved in oxidative phosphorylation. Carbonic anhydrase was also found active in OS discs. Moreover, colocalization of Rhodopsin with respiratory complex I and ATP synthase seems a further step in the characterization of some proteins typical of the mitochondrial inner membranes that are expressed in the rod discs. The existence of oxygen utilization in the outer retina, likely supplying ATP for phototransduction, may shed light on some retinal pathologies related to oxidative stress of the outer retina. Copyright © 2013 John Wiley & Sons, Ltd.